2009
DOI: 10.1029/2008gb003381
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nitrogen balances for six shrublands across Europe

Abstract: [1] Shrublands constitute significant and important parts of European landscapes providing a large number of important ecosystem services. Biogeochemical cycles in these ecosystems have gained little attention relative to forests and grassland systems, but data on such cycles are required for developing and testing ecosystem models. As climate change progresses, the potential feedback from terrestrial ecosystems to the atmosphere through changes in carbon stocks, carbon sequestration, and general knowledge on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 67 publications
6
37
2
Order By: Relevance
“…These estimates are within the range of published C sequestration values, with similar shrub-dominated sites ranging from 0.3 to − 2.9 t C ha −1 yr − 1 (Larsen et al, 2007;Beier et al, 2009;Kiely et al, 2009) and upland graminoid dominated sites ranging from −0.1 to −6.4 t C ha −1 yr −1 (Fitter et al, 1997;Flanagan and Johnson, 2005;Allard et al, 2007;Soussana et al, 2007;Kiely et al, 2009).…”
Section: Net Carbon Sequestration Within Graminoid-and Calluna-dominasupporting
confidence: 63%
“…These estimates are within the range of published C sequestration values, with similar shrub-dominated sites ranging from 0.3 to − 2.9 t C ha −1 yr − 1 (Larsen et al, 2007;Beier et al, 2009;Kiely et al, 2009) and upland graminoid dominated sites ranging from −0.1 to −6.4 t C ha −1 yr −1 (Fitter et al, 1997;Flanagan and Johnson, 2005;Allard et al, 2007;Soussana et al, 2007;Kiely et al, 2009).…”
Section: Net Carbon Sequestration Within Graminoid-and Calluna-dominasupporting
confidence: 63%
“…In this ecosystem, the C root/shoot ratio ranged between 0.17 and 0. budget at all J. tridens shrubland sites and ranged from 70 (for 10-20% shrub cover) to 160 Mg C ha -1 (for 60-70% shrub cover) where soil C constitutes more than 90% of the total carbon in the ecosystem. This is consistent with Beier et al (2009) who reported that soil C constitutes 95% of the total carbon in six shrublands along a climatic gradient across the European continent.…”
Section: Shrublandsupporting
confidence: 81%
“…In addition to the management related import and export, gaseous exchange in many different forms (e.g., NO, NO 2 , HNO 3 , N 2 O, NH 3 , and N 2 ), as well as input by rain and leaching of N-compounds with the soil water, had been measured. Beier et al (2009) presented N balances of six shrublands along a climatic gradient across the European continent. Nitrogen storage was also dominated by the soil pools, generally showing small losses except when atmospheric N input was high.…”
Section: Introductionmentioning
confidence: 99%